The Influence of Motivation and Work Discipline on Performance with Work Environment as a Mediating Variable at CV Femarse Inti Mulia - Veronika T Batubara; Zainul Kisman (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2026)
This study examines the influence of work motivation and work discipline on employee performance, with the work environment as a mediating variable at CV Femarse Inti Mulia. Using a quantitative cross-sectional approach, all 58 employees were included as respondents through a census method. Data were collected using a Likert-scale questionnaire and analyzed with SEM-PLS. The results show that work motivation and work discipline both have positive and significant effects on employee performance. Motivation and discipline also significantly influence the work environment. Additionally, the work environment positively affects performance. Mediation analysis reveals that the work environment mediates the effect of work motivation on performance but does not mediate the effect of work discipline. These findings indicate that employee performance is shaped not only by motivation and discipline but also by the quality of the work environment.